Evaluation of Three Atlantic Salmon Strains for Resistance to Copepodid Sea Lice Attachment - Michael R. Pietrak; Thomas A. Delomas; Demitri Lifgren; Mark P. Polinski (Fishes)
Sea lice have been a persistent pest of the salmon farming industry for more than 50 years. In this study, we aimed to identify if different strains of Atlantic salmon with discrete long-term lice exposure histories had variable resistance to copepodid attachment and/or different attachment-specific transcriptome patterns. We additionally sought to characterize lice distributions on fins, head, and skin and identify if attachment location influenced transcriptomic profiles of lice. Lice counts were correlated with body size and highest on St. John River (SJR; open ocean-run) relative to Grand Lakes Stream (GLS; 200-year restricted ocean-run) or Sebago Lake (CAS; ~11,000 years landlocked) Atlantic salmon. However, lice density was similar between strains. Skin and fins had expectedly different transcriptomic profiles; however, notable differences were not observed between salmon strains. Variance in lice transcriptomes was minimally affected by attachment location even though lice strongly preferred fins relative to head or body. Attached lice did have different transcriptomic profiles on GLS relative to CAS or SJR. This study cumulatively identified a minimal host evolutionary component for sea lice attachment resistance, although lice behavior post-attachment appeared somewhat affected by strain. Non-uniform settlement distributions and tank-specific variability in lice attachment were observed across populations.